Speckle-based x-ray phase-contrast imaging with a laboratory source and the scanning technique - Zhou, Tunhe; Zanette, Irene; Zdora, Marie-Christine; Lundstrom, Ulf; Larsson, Daniel H.; Hertz, Hans M.; Pfeiffer, Franz; Burvall, Anna (Optics Letters, 2015)
The speckle-based scanning method for x-ray phasecontrast imaging is implemented with a liquid-metal-jet source. Using the two-dimensional scanning technique, the phase shift introduced by the object is retrieved in both transverse orientations, and the limitations on spatial resolution inherent to the speckle-tracking technique are avoided. This method opens up possibilities of new highresolution multimodal applications for lab-based phasecontrast x-ray imaging.
CRIS-Team Scopus Importer:2023-03-08